Certification in Testing Program - Bezanson, M. Lynne; Busque, Guy; Jean, Jr., Paul; Monsebraaten, Arthur J. (Canadian Journal of Counselling and Psychotherapy, 1980)
In 1977, the Canada Employment and Immigration Commission (CEIC) implemented a Certification in Testing Program which is offered to all employment counsellors working in Canada Employment Centres (CECs) across the country. Employment counsellors enter the competency-based program on a voluntary basis and may elect to follow it in English or in French. The program includes (a) a 30-hour self-study package, (b) a 3½ day group training course, (c) a formal assessment of the participant's competencies in interpreting CEIC approved tests, and (d) the recognition of successful counsellors through the awarding of a CEIC certificate in testing. By June 1980, over 1,000 employment counsellors had been certified. This article outlines the history, development, implementation procedures and evaluation instruments used in the program.